Age-adjusted risk factors are independently associated with an increased risk of ischaemic stroke, transient ischaemic stroke and systemic embolism in the ETNA-AF-Europe registry. (14th October 2021) - De Caterina, R; De Groot, J.R; Weiss, T.W; Kelly, P; Monteiro, P; Deharo, J.C; De Asmundis, C; Lopez-De-Sa, E; Waltenberger, J; Steffel, J; Levy, P; Bakhai, A; et al.
Abstract: Background: Oral anticoagulation is highly effective in preventing ischaemic stroke in patients with atrial fibrillation, but 1–2% of the patients suffer an ischaemic stroke upon anticoagulation. Outcomes are further influenced by various factors, and recent research has focussed on identifying risk factors that could be helpful in predicting stroke outcomes in anticoagulated patients. This could further assist clinicians in timely identification and management of high-risk patients. Purpose: The present analysis aims to assess the age-adjusted risk predictors of ischaemic stroke and systemic embolic events (SEE) (including transient ischaemic attack [TIA]) during two-year follow-up of unselected European patients with AF in the ETNA-AF-Europe registry. Methods: ETNA-AF-Europe is a prospective, multi-centre, post-authorisation, observational study conducted in 825 centres enrolling patients treated with edoxaban once daily in 10 European countries. Wald Chi square tested the association between risk predictors and stroke and SEE after adjusting for age, given that age is a well-known, strong predictor of stroke. Results: A total of 13, 417 patients with AF (edoxaban 60 mg: n=10, 248; edoxaban 30 mg: n=3169) completed the two-year follow-up. The mean age was 73.6±9.5 years, with ∼84% of the patients aged over 65 years. The mean weight was 81.0±17.3 kg, estimated glomerular filtration rate was 74.4±30.5 ml/min/1.73m 2 and males were 56.6%. The mean CHA2DS2-VASc and HAS-BLED scores were 3.2 and 2.5, respectively. Univariate analysis demonstrated that history of TIA at baseline was the strongest age-adjusted predictor of stroke and SEE (Wald Chi-square: 77.69; p<0.0001) (Figure 1), followed by CHA2DS2-VASc score (41.09; p<0.0001) (Figure 2), history of ischaemic stroke (29.47; p<0.0001), history of any stroke (all strokes combined including stroke of unknown/unspecified type) (29.18; p<0.0001), subjective frailty as assessed by physician (20.60; p<0.0001), and HAS-BLED score (17.22; p<0.0001). Conclusion: History of TIA, CHA2DS2-VASc score, history of stroke, frailty and HAS-BLED score are independently associated with an increased age-adjusted risk of ischaemic stroke, TIA and SEE in anticoagulated patients with AF. These findings highlight the importance of optimising anticoagulation therapy in secondary prevention of TIA and in patients with high CHA2DS2-VASc scores, ensuring the correct use of NOACs - adherence and correct dosing - in this high-risk population. These findings also suggest that additional therapies could be needed to prevent stroke in this population. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Daiichi Sankyo Europe GmbH